Examining the feasibility of the integrated hope scale in American college students. Issue 3 (3rd July 2018) - Ingram, Paul B.; Warlick, Craig A.; Ternes, Michael S.; Krieshok, Thomas S.
Abstract : The Integrated Hope Scale (IHS) provides a multi-dimensional evaluation of factors common across measures of hope, examining social relationships, trust and confidence, perspectives of the future, and a lack of hopefulness. Despite promise for the instrument's utility, research on the IHS is sparse has been limited to non-English-speaking populations, requiring translated items, and the cross-cultural transportability of hope constructs has previously been raised. Predominant theories of hope used in American populations have been criticized for not measuring important aspects that are included within the IHS. Using confirmatory factor analysis and latent class analysis, this study explored the IHS's structural integrity and interpretive potential using a regionally and racially diverse sample of American college students. Results suggest that the IHS offers a valid global assessment of hope as well as for targeted measurement of discrete areas identified by instrument factor scores. The IHS also shows promise in differentiating individuals according to their level of hopefulness.